A GPU-Based Wide-Band Radio Spectrometer. (4th December 2014) - Chennamangalam, Jayanth; Scott, Simon; Jones, Glenn; Chen, Hong; Ford, John; Kepley, Amanda; Lorimer, D. R.; Nie, Jun; Prestage, Richard; Roshi, D. Anish; Wagner, Mark; Werthimer, Dan
Abstract: The graphics processing unit has become an integral part of astronomical instrumentation, enabling high-performance online data reduction and accelerated online signal processing. In this paper, we describe a wide-band reconfigurable spectrometer built using an off-the-shelf graphics processing unit card. This spectrometer, when configured as a polyphase filter bank, supports a dual-polarisation bandwidth of up to 1.1 GHz (or a single-polarisation bandwidth of up to 2.2 GHz) on the latest generation of graphics processing units. On the other hand, when configured as a direct fast Fourier transform, the spectrometer supports a dual-polarisation bandwidth of up to 1.4 GHz (or a single-polarisation bandwidth of up to 2.8 GHz).